KEWENANGAN PENGADILAN NEGERI DALAM MENETAPKAN TERSANGKA MELALUI PRAPERADILAN - Alviona Vinda Safira; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Judge position is the most important thing to decide cases in trial which guaranteed by statutory regulations. Mostly, judges in giving decisions are not in accordance with legal facts, even exceeding their authority. In judicial practice, for example in pretrial review, judges are bound to the object of pretrial review. Pretrialreview is an institution that was born to carry out surveillance actions against law enforcement, therefore in implementing their authority, law enforcement does not make of any abuse of power.Pretrial reviews are regulated in Article 77 of the Criminal Procedure Code, as well as other laws and regulations as an expansion of pretrial reviews objects. One example of a pretrial case that caught public's attention was a pretrial by a non-governmental organization against the KPK in Century Bank case, which in its petition, requested that the Court through the Pre-trial set a person or group of people to be suspected of corruption case.The author is interested in exploring this case to examine the authority of the District Court in determining suspects through pretrial reviews and understanding the legal consequences, if the pretrial decision is not carried out by the Respondent, in this case, KPK. The research method used by the author is a normative research that examines the norms, laws and regulations and also the literature.Determination of a person becomes a suspect, based on the law must be carried out by investigators, such as the police, prosecutors, and even the KPK to conduct the process of determining the suspect. In the Pre-trial review, Judges to give decisions based on laws, that apply to the principle of legality and the judge's logic and conscience. However, obstacles are often encountered in pretrial practices, such as weak law enforcement to the emergence of a legal vacuum and weak law enforcement in handling corruption cases, the result, someone may continuously obtaining the suspect “label” without further processing.aforementioned, Judge is expected to be more careful in deciding with applicable procedures and regulations, also in carrying out his judicial duties professionally and objectively so the verdict based on the word “For the sake of Justice based on the Almighty God”. There is an expectation to KPK can uncover and resolve the corruption cases professionally without violating someone legal rights.Keywords: Judicial Power, Determination of Suspects, Pretrial Review, KPK